A produção de textos na educação básica: desenvolvendo as capacidades de linguagem - COSTA, Alex de Castro da (2023)
The present work addresses the practice of writing/rewriting in Basic Education, proposing an intervention in school texts through the teaching of the textual genre opinion article, based on the theoretical-methodological assumptions of Sociodiscursive Interactionism. The research was conducted with 9th-grade students from a public school in the city of Pio XII-MA. The central question of the research is: what difficulties do 9th-grade students from a public school in Pio XII/MA face when mobilizing their language abilities in the production of opinion articles? Consequently, the general objective is to: promote the communicative competence of 9th-grade students through the practice of writing/rewriting texts. The specific objectives are: to use interactive textual correction and the list of findings as regulators of the text production process, verify the mobilization of the language abilities of the students in the production of opinion articles, employ didactic sequences as an auxiliary tool in text production at school, and investigate in what way didactic sequences contribute to the production of the students' texts. In line with the proposed objectives, the research adopts a qualitative methodological perspective, which, according to Lara and Molina (2011), aims for a direct investigation of data in their natural environment. Therefore, from the standpoint of the research problem approach, the investigation carried out is qualitative and collaborative, thus classified as action research. As for the technical procedures, bibliographic research is employed. The theoretical framework supporting this work is anchored in the studies of Bronckart (1999), Dolz and Schneuwly (1999, 2004, 2004b), Cristovão (2001, 2007), Machado (2004), Machado and Cristovão (2006), Gonçalves and Barros (2010), Barros (2012), Gonçalves and Ferraz (2014), Nascimento and Pereira (2014), Gonçalves (2007, 2011), among other authors. The results of the study revealed a significant evolution between the students' first and last productions, thus demonstrating an improvement in their communicative competence and a considerable development of their language abilities (action abilities, discursive abilities, and linguistic-discursive abilities).